Israel after Begin - Mahler, Gregory S., 1950- (State University of New York Press, 1990)
Annotation Fourteen contributions on the nature of Israeli politics in the post- Begin era discuss such topics as: the withdrawal of Israeli forces from Lebanon; the harnessing of the enormous inflation rate; the relationship between Israel and the US; the survival of the Likud Party; tension between religious and secular Israeli Jews; and changes in national electoral strategies of the major parties. Most of the papers (revised for inclusion) were presented at the Israel Studies Association Conference held at the U. of Vermont, June 1987. Paper edition (unseen), $18.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Begin, Menachem, -- 1913-1992 -- Congresses.; Begin, Menachem, -- 1913-1992; Israel -- Politics and government -- Congresses.; Israel -- Foreign relations -- Congresses.; Political parties -- Israel -- Congresses.; Israël -- Politique et gouvernement -- Congrès.; Israël -- Relations extérieures -- Congrès.; HISTORY.; Diplomatic relations; Political parties; Politics and government; Israel; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.